The impact of government expenditure on economic growth in Barbados : a disaggregated approach - Belgrave, Anton ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Uses Barbadian data and the cointegration methodology to examine the effects of the composition of government expenditure on economic growth by disegregating the level of government expenditure into functional and economic categories.